Perception of call center agents towards effective training program - Miranda, Jasmin T.; Malicdem, Eleanor A. (2007.)
This study seeks to determine an effective training program for communicative skills as perceived by call center agents, and to propose a training program based from the results of the study. This study followed the simple random sampling procedure in selecting the respondents. The sample consists of eighty (80) call center agents. The study utilized a survey questionnaire that consists of communicative skills namely Voice, Articulation and Grammar, needed for telemarketing. Five lessons describe each skill. The respondents were asked to rank the lessons from least to most important using a scle of 1 to 5, 1 being the least important and 5 being the most important. Mean Ranking and Mode were used to determine the rankings of the lessons and to identify how these lessons will be arranged in the proposed training program. The findings of the study showed that the most important communicative skills needed for call center agents to perform their job efficiently were Pronunciation uder the skill Voice, American Vowels and Consonants under the skill Articulation, and Colloquial Expressions under the skill Grammar. Therefore, these lessons have the same time allotment and were given most emphasis and focus on the proposed training program.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Employees -- Training of -- Psychological aspects; Call centers -- Philippines -- Employees